Effect of Exercise on Morphine-Induced Toxicity in Rat Liver and Kidney - Massumeh Ahmadizadeh; Alireza Sarkaki; Yagoub Farboud; Babak Mohammadian; Fakher Rahim (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2012)
Background and Objective: Morphine induces adverse effect in many organs. It has been known that moderate exercise reduces oxidative stress. The present study was undertaken to evaluate the effect of exercise on morphine-produced toxicity in rat liver and kidney.Subjects and Methods: Adult male rats were randomly divided in 4 groups including: (1) morphine-treated, (2) morphine-treated+exercise, (3) vehicle (normal saine) treated, (4) vehicle treated+exercise. Animals in groups of 1 and 2 received morphine (ip) two times per day for 5 consecutive days. 1st day 5mg/kg, 2nd day10 mg/kg, 3rd day 20mg/kg, 4th day 40mg/kg and 5th 50mg/kg. Rats in groups of 3 and 4 received vehicle only. The animals in groups of 2 and 4 were participated in the treadmill exercise sessions (1 h at speed 17m/min) for 10 consecutive days. 24 h later, the animals were killed with overdose of sodium pentobarbital. Blood was collected for determination of ALT, AST, ALP, BUN and creatinine. Liver and kidney tissues were removed, fixed and processed for light microscopy. Ten animals were used for each group.Results: Biochemical and histopathological observations indicated that morphine produced injury in the liver and the kidney. Exercise reduced morphine -induced toxicity (P<0.05).Conclusion: Morphine- induced toxicity in rat liver and kidney. Execise protected liver and kidney against morphine-induced toxicity. Blocking of oxidative damage by exercise may be a useful strategy for preventing morphine adverse effects.